2019
DOI: 10.21273/horttech04374-19
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Vegetable Amaranth in Diverse Tanzanian Production Environments

Abstract: Amaranth (Amaranthus sp.) is an important leafy vegetable in Africa where most farmers grow unimproved landraces. Information about amaranth genetic diversity and its adaptation to different environments will help breeders develop improved commercial varieties that meet market requirements. The objectives of this study were to investigate the performances of amaranth entries for vegetable yield across locations and seasons, assess the relative contributions of genetic vs. env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
4
9
2
Order By: Relevance
“…cruentus , respectively [ 59 ]. The four amaranth species were chosen because of their genetic diversity (variation), contrasting plant architecture (morphology), and since they are taxonomically well characterised and commercially important in East Africa [ 52 , 53 , 57 , 60 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…cruentus , respectively [ 59 ]. The four amaranth species were chosen because of their genetic diversity (variation), contrasting plant architecture (morphology), and since they are taxonomically well characterised and commercially important in East Africa [ 52 , 53 , 57 , 60 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…Urea (46N-0P-0K) was applied as sidedressing 3 weeks after transplanting at the rate of 120 kg•ha À1 . At Chambezi and Malolo (the coastal zone sandy soil trial locations), decomposed cow dung was applied during plot preparation immediately before transplanting at the rate of 2.75 kg•m À2 according to local practice because these soils are low in total soil nitrogen, organic carbon, and clay contents (Dinssa et al, 2019). DATA COLLECTION.…”
Section: Methodsmentioning
confidence: 99%
“…Gender-disaggregated participatory maize (Zea mays) variety trials conducted in Benin, Nigeria, and Mali identified gender-shared and distinct varietal traits (Tegbaru et al, 2020). Dinssa et al (2019) reported high differential performance of amaranth lines across Tanzanian environments differing in mean temperatures, rainfall, soil types, and other factors and identified two mega-environments: relatively high-altitude cool environments and coastal and low-altitude environments characterized by high temperatures. This indicated the need to select varieties adapted to each of the two contrasting mega-environments identified as target selection areas in Tanzania.…”
mentioning
confidence: 99%
“…Amaranth, known in Tanzania by various local names such as 'Mchicha', is a popular traditional African leafy vegetable with a long cultural tradition in East Africa and other regions on the continent. The leaves are a source of fiber, vitamin A, vitamin K, vitamin B, vitamin C, potassium, calcium, zinc and iron, some of which are deficient in local diets (Dinssa et al, 2019).…”
Section: Amaranthmentioning
confidence: 99%